PENATALAKSANAAN HOLISTIK PADA WANITA 47 TAHUN DENGAN DERMATITIS KONTAK IRITAN DAN PITYRIASIS VERSICOLOR MELALUI PENDEKATAN DOKTER KELUARGA DI WILAYAH PUSKESMAS RAWAT INAP GEDONG TATAAN - Khairunnisa Salsabila; Sahab Sibuea; Imelda Carolia (Fakultas Kedokteran Universitas Lampung, 2025)
Irritant contact dermatitis (ICD) is an inflammation of the skin that occurs due to exposure to irritant substances or materials. This condition can be experienced by anyone, regardless of age, gender, or race. The main treatment for ICD is to identify and avoid exposure to the irritant that triggers it. Using a comprehensive and integrated family medicine approach to identify risk factors and clinical problems, and conducting patient management based on evidence-based medicine, with a patient-centered, family-involved, and community-oriented approach. This study uses a case report approach as a form of analysis. Primary data were collected through anamnesis and physical examination, while secondary data came from patient medical records at the Health Center. Evaluation was carried out quantitatively and qualitatively based on a holistic diagnosis that included the initial stage, process, and end of the study. Mrs. S, 47 years old, came to the Gedong Tataan Health Center with complaints of red and itchy spots on both palms accompanied by peeling skin since 2 weeks ago, accompanied by other complaints of white spots on both cheeks accompanied by itching. The patient was worried that the complaints would persist and could interfere with her daily activities. The patient is a dawet seller. The patient was diagnosed with irritant contact dermatitis and pityriasis versicolor based on anamnesis and physical examination. Non-drug and drug interventions were performed on the patient and her family with education related to the patient's disease in three home visits. Comprehensive management with a family medicine approach has been applied to Mrs. S, 47 years old, who experienced irritant contact dermatitis and pityriasis versicolor, according to the results of the initial holistic diagnosis. The interventions provided succeeded in increasing the patient's understanding and encouraging behavioral changes in the patient and her family members.